Epimedium sagittatum Maxim ameliorates adriamycin‐induced nephropathy by restraining inflammation and apoptosis via the PI3K/AKT signaling pathway - Ru Wang; Mengnan Zeng; Beibei Zhang; Qinqin Zhang; Shuangshuang Xie; Yingbo Hu; Ruyi Fan; Mengya Wang; Xiao Yu; Yuhan Zhang; Xiaoke Zheng; Weisheng Feng (Immunity, Inflammation and Disease)
Abstract Background Modern pharmacological studies show that Epimedium sagittatum Maxim (EPI) has antioxidant, antiapoptotic, anti‐inflammatory effects. However, the effects of EPI on adriamycin‐induced nephropathy are unclear. Aim The main purpose of this study is to investigate the effects of EPI on adriamycin‐induced nephropathy in rats. Methods The chemical composition of EPI was detected by high performance liquid chromatography. Network pharmacology was used to collect the effects of EPI on adriamycin nephropathy; renal histological changes, podocyte injury, inflammatory factors, oxidative stress levels, apoptosis levels, and the PI3K/AKT signaling pathway were examined. Moreover, analyze the effects of icariin (the representative component of EPI) on adriamycin‐induced apoptosis and PI3K/AKT signaling pathway of NRK‐52e cells. Results Network pharmacological results suggested that EPI may ameliorate adriamycin‐induced nephropathy by inhibiting inflammatory response and regulating the PI3K/AKT signaling pathway. The experimental results showed that EPI could improve pathological injury, renal function, podocyte injury, and inhibit inflammation, oxidative stress, apoptosis in adriamycin‐induced nephropathy rats through the PI3K/AKT signaling pathway. Furthermore, icariin inhibited adriamycin‐induced mitochondrial apoptosis in NRK‐52e cells. Conclusion This study suggested that EPI ameliorates adriamycin‐induced nephropathy by reducing inflammation and apoptosis through the PI3K/AKT signaling pathway, icariin may be the pharmacodynamic substance basis for this effect.